2017
DOI: 10.1002/cctc.201701238
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Catalytic Oxygen Activation by Localized Surface Plasmon Resonance: Effect of Visible Light Pre‐treatment and Bimetallic Interactions

Abstract: Visible light pre‐treatment has been found to be capable of enhancing the catalytic oxygen activation on AuPt/TiO2 by up to seven times. Visible light pre‐treatment exploits the localized surface plasmon resonance effect of Au to generate free electrons, which are transferred to the Pt active sites. The electron transfer was evident from a change in Pt speciation observed from X‐ray photoelectron spectroscopy, showing the presence of PtO after visible light pre‐treatment. Photoluminescence spectroscopy was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…Consequently, the oxidation state of K may be an underlying reason behind the shifting selectivity due to changes in intermediate stability [52]. The proposed K to Ni electronic pathway agrees with the work function-driven electron transfer mechanism observed in our earlier works on bimetallic alloys [53,54], resulting in the decreased H 2 TPR peak for the reduction of Ni 2+ into Ni 0 .…”
Section: Role Of Potassium Substitution In Changing Reaction Selectivitysupporting
confidence: 87%
“…Consequently, the oxidation state of K may be an underlying reason behind the shifting selectivity due to changes in intermediate stability [52]. The proposed K to Ni electronic pathway agrees with the work function-driven electron transfer mechanism observed in our earlier works on bimetallic alloys [53,54], resulting in the decreased H 2 TPR peak for the reduction of Ni 2+ into Ni 0 .…”
Section: Role Of Potassium Substitution In Changing Reaction Selectivitysupporting
confidence: 87%
“…Such a plasmonic effect is expected to enhance the photoactivity upon visible light illumination. 42,43 With the plasmonic Au-TiO 2 catalyst in hand, we started investigating the envisioned photocatalytic oxidation of organosilanes. Dimethylphenylsilane (1a) was used as a model substrate in the envisioned photocatalytic oxidation of silane (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…UV–vis diffuse reflectance spectroscopy of Au-TiO 2 showed a distinct absorption band occurring at approximately 560 nm compared to bare TiO 2 , which is associated with the localized surface plasmon resonance (LSPR) of Au nanoparticles (Figure S7). Such a plasmonic effect is expected to enhance the photoactivity upon visible light illumination. , …”
Section: Resultsmentioning
confidence: 99%
“…As both Ni and Ag are known to be highly prone to uncontrolled oxidation when exposed to air without any protection measures, , the catalysts were passivated in a controlled oxidation step prior to XPS analysis. The change in oxidation states or local electron densities was then compared on the basis of other findings on the effect of light pretreatment on AuPt/TiO 2 . , The previous findings demonstrated that a higher electron density surface was more favorable to oxygen activation, leading to catalyst surface oxidation. Consequently, a catalyst with a more oxidized surface after passivation implies a higher electron density than in its original state.…”
Section: Resultsmentioning
confidence: 99%